Overconfidence and narcissism among the upper echelons: a systematic literature review - Johannes Brunzel (Management Review Quarterly, 2020)
Research has been trying to analyze cognitive decision making processes of top-executive for decades. In particular, economic and organizational research on overconfidence (e.g., the notion that one is better than the average) and narcissism (e.g., exaggerated feeling of self-importance and the need for admiration) among the upper echelons has shown to influence firm strategies and firm level outcomes in similar ways. Yet these approaches appear in distinct research disciplines. Although both constructs are theoretically and empirically linked, and have shown to affect key organizational outcomes, surprisingly little clear empirical consensus exist how these constructs—individually and mutually—affect firm level outcomes. I try explain this puzzle by providing an overview of the leading approaches of executive overconfidence and executive narcissism research. To disentangle both constructs conceptionally and empirically, I review a large sample of articles that are nested in leading economic and business journals. Thus, I identify key operationalization issue and discuss how divergent literature streams in Economics and Organizational Behavior may benefit from each other. The review suggest that paying more attention—theoretically and empirically—to the interaction of overconfidence and narcissism may help to augment knowledge accumulation in the field. Furthermore, greater validation concerns of unobtrusive measures and its endogenous nature may help to rule out alternative explanations. Generally speaking, the results suggest that top-executive overconfidence and narcissism are not mere interesting psychological biases but affect firm-level outcomes in important ways.
Keywords: E45; 650; Overconfidence; Narcissism; Upper-Echelon; Top-Executives